Inhibition of Alk signaling promotes the induction of human salivary-gland-derived organoids - Shohei Yoshimoto; Junko Yoshizumi; Hiromasa Anzai; Koichiro Morishita; Kazuhiko Okamura; Akimitsu Hiraki; Shuichi Hashimoto (The Company of Biologists, 2020)
Hyposalivation and xerostomia are the cause of several morbidities, such as dental caries, painful mucositis, oral fungal infections, sialadenitis and dysphagia. For these reasons, preservation of normal saliva secretion is critical for the maintenance of functionally normal oral homeostasis and for keeping good health. Several strategies for restoring salivary gland function have been reported, from different points of view, based on the use of salivary-gland-derived epithelial stem/progenitor cells and tissue engineering approaches to induce organoids that mimic in vivo salivary glands. In this study, we clarified that inhibition of activin receptor-like kinase (Alk) signaling was essential for the induction of human salivary-gland-derived organoids, and demonstrated the usefulness of such organoids as an inflammatory disease model. In inflammatory conditions like sialadenitis, in general, pro-inflammatory cytokines such as tumor necrosis factor-α (TNF-α, also known as TNF) are upregulated, but their function is still unclear. In our established human salivary-gland-derived organoid culture system, we successfully induced organoid swelling by stimulation with carbachol, a non-selective cholinergic agonist, and forskolin, an activator of cystic fibrosis transmembrane conductance regulator (CFTR). Furthermore, we found that this organoid swelling was inhibited by TNF-α. From these results, we could clarify the inhibitory function of TNF-α on saliva secretion in vitro. Thus, our established human salivary-gland-derived organoids would be useful for in vitro analyses of the morphological and functional changes involved in salivary gland dysfunctions in several research fields, such as pathobiology, inflammation and regenerative medicine. This article has an associated First Person interview with the first author of the paper.